Risk analysis of fluctuating hypercalcemia after leukapheresis in cellular therapy - Tomoyasu Jo; Yasuyuki Arai; Toshio Kitawaki; Momoko Nishikori; Chisaki Mizumoto; Junya Kanda; Kouhei Yamashita; Miki Nagao; Akifumi Takaori-Kondo (Scientific Reports, 2023)
Abstract Optimized management of citrate-induced hypocalcemia is required to provide safe leukapheresis. We prospectively analyzed subjects who underwent leukapheresis for cytotherapy, and evaluated serum ionized (iCa) concentrations before, at the end of, and 1 h after leukapheresis. During leukapheresis, calcium gluconate solution was continuously supplemented intravenously with hourly measurement of iCa. 76 patients including 49 lymphapheresis for chimeric antigen receptor T-cell therapy and 27 stem cell collections were enrolled. Median processing blood volume was 10 L (range, 6–15 L). Fluctuating hypercalcemia, in which the iCa concentration rose above its upper limit 1 h after leukapheresis, was observed in 58 subjects (76.3%). Multivariate analysis revealed that higher ratios of processing blood volume to body weight, more rapid calcium supplementation, and lower iCa concentration at the end of leukapheresis significantly increased elevation of serum iCa concentration by 1 h after leukapheresis. Based on multivariate analyses, we developed a formula and a diagram that accurately estimates serum iCa concentration 1 h post-leukapheresis. This suggests optimal targets for iCa concentration and calcium supplementation rates. In cases with high ratios of processing blood volume to body weight, slowing the rate of blood processing, rather than increasing calcium supplementation should safely alleviate hypocalcemia during leukapheresis without inducing hypercalcemia thereafter.